ANALISIS KETERSEDIAAN ALAT PELINDUNG DIRI (APD) UNTUK MENGATASI PANDEMI COVID-19 DI RUMAH SAKIT RAJAWALI CITRA DAERAH ISTIMEWA YOGYAKARYA - Fathoni, Muhammad Isnaini; Purwanta, Purwanta; Mardiyah, Kofsatun; Kuswanto, Kuswanto (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
This study aims to determine the availability of Personal Protective Equipment (PPE) to overcome the covid-19 pandemic. This research uses a qualitative method. The results show that the availability of personal protective equipment to overcome the covid-19 pandemic at the Rajawali Citra Hospital in the Special Region of Yogyakarta must be of high quality and according to standards. The process of providing PPE at the Rajawali Citra Hospital in Yogyakarta has 2 ways, namely: 1. Procuring it yourself: ordering PPE from distributors 2. through grants or assistance from the Health Office or from donors.